Response Surface Methodology as a Tool for Optimization of self-nanoemulsified Drug Delivery System of Quetiapine Fumarate - Talele, Swati G. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The objective of the present study was to design self nanoemulsifying drug delivery system of quetiapine fumarate by optimizing particle size, zeta potential, and drug release using response surface methodology. Materials and Methods: Self-nanoemulsified drug delivery system formulations were prepared using Labrafac Lipophile WL as oil, Tween 80 as a surfactant, and Capryol 90 as a cosurfactant. Pseudo-ternary phase diagrams of oil, surfactant/co surfactant, and water were developed using the water titration method. Different Smix ratios were prepared, and the maximum ratio was selected for self-nanoemulsified drug delivery system (SNEDDS) formulation. D-optimal design for 3 factors at 3 levels each was employed systematically to optimize particle size, zeta potential, and drug release. Result and Discussion: The polynomial mathematical model generated for response and found to be significant. The optimized model predicted a particle size 54.42 nm, zeta potential âˆ’13.03 mv, and drug release 93.67% residual plots for particle size, zeta potential, and % drug release indicates points nearly closed to straight lines indicating good model. The signal-to-noise ratio effect was studied which causes r2 value closer to 0.5. Conclusion: The quantitative effect of these factors at different levels was predicted using polynomial equation. Response methodology was then used to predict the levels of the factors A, B, and C required to obtaining an optimum formulation. A new formulation was prepared according to these levels. Signal-to-noise ratio was studied. Observed response was in close agreement with the predicted values of the optimized formulation, thereby demonstrating the feasibility of the optimization procedure in developing SNEDDS of quetiapine fumarate.